Isocitrate dehydrogenase gene variants in cancer and their clinical significance - Cadoux-Hudson, T; Schofield, C; McCullagh, JSO (Portland Press, 2021)
Human isocitrate dehydrogenase (IDH) genes encode for the IDH1, 2 & 3 isoenzymes which catalyse the formation of 2-oxoglutarate from isocitrate and are essential for normal mammalian metabolism. Although mutations in these genes in cancer were long thought to lead to a ‘loss of function’, combined genomic and metabolomic studies led to the discovery that a common IDH 1 mutation, present in low-grade glioma and acute myeloid leukaemia (AML), yields a variant (R132H) with a striking change of function leading to the production of (2R)-hydroxyglutarate (2HG) which consequently accumulates in large quantities both within and outside cells. Elevated 2HG is proposed to promote tumorigenesis, although the precise mechanism by which it does this remains uncertain. Inhibitors of R132H IDH1, and other subsequently identified cancer-linked 2HG producing IDH variants, are approved for clinical use in the treatment of chemotherapy-resistant AML, though resistance enabled by additional substitutions has emerged. In this review, we provide a current overview of cancer linked IDH mutations focussing on their distribution in different cancer types, the effects of substitution mutations on enzyme activity, the mode of action of recently developed inhibitors, and their relationship with emerging resistance-mediating double mutations.